2019
DOI: 10.3390/genes10110919
|View full text |Cite
|
Sign up to set email alerts
|

X-Linked Emery–Dreifuss Muscular Dystrophy: Study Of X-Chromosome Inactivation and Its Relation with Clinical Phenotypes in Female Carriers

Abstract: X-linked Emery–Dreifuss muscular dystrophy (EDMD1) affects approximately 1:100,000 male births. Female carriers are usually asymptomatic but, in some cases, they may present clinical symptoms after age 50 at cardiac level, especially in the form of conduction tissue anomalies. The aim of this study was to evaluate the relation between heart involvement in symptomatic EDMD1 carriers and the X-chromosome inactivation (XCI) pattern. The XCI pattern was determined on the lymphocytes of 30 symptomatic and asymptoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
(65 reference statements)
0
5
1
Order By: Relevance
“…Viggiano et al 25 reported a cross-sectional cohort of 30 female EMD variant-carriers with one-third over 50 years of age. Seventeen per cent had cardiac involvement (first- or second-degree AV block not requiring a pacemaker), all of whom were over 50 years of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Viggiano et al 25 reported a cross-sectional cohort of 30 female EMD variant-carriers with one-third over 50 years of age. Seventeen per cent had cardiac involvement (first- or second-degree AV block not requiring a pacemaker), all of whom were over 50 years of age.…”
Section: Discussionmentioning
confidence: 99%
“… 28 , 29 Marked reduction in the emerin content of lymphocytes and lymphoblastoid cell lines have been described in a female carrier, 30 but in a study of 28 symptomatic and asymptomatic female carriers, skewed X-inactivation in EMD did not correlate with cardiac symptoms. 25 The authors acknowledged that the X-inactivation pattern in lymphocytes may not reflect that in cardiac tissues. More recent work in a symptomatic female carrier of a truncating EMD variant demonstrated a mixed population of emerin-positive and emerin-negative myoblasts, ruling out skewed X-inactivation as a mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the type of cardiac involvement, cardiomyopathy or conduction system defects, was not specified; third, it cannot ruled out that the XCI pattern analyzed in leukocytes is not always useful to predict carrier phenotypes or disease progression. XCI is usually assessed in leukocytes from peripheral blood because it is the most common source of DNA supply, but, as suggested for EDMD1 carriers [ 145 ], the discordance between cardiac phenotype (conduction system defects) and degree of the XCI can be explained as likely depending by the different embryological origin of the tissues analyzed (constituents of the conduction cardiac tissue and blood).…”
Section: Discussionmentioning
confidence: 99%
“…Emerin is a nuclear inner membrane protein whose gene mutations are related to Emery-Dreifuss Muscular Dystrophy, an X-linked disease [67]. Tifft and coworkers demonstrated that emerin function is regulated by several tyrosine kinases, including Her2, Src and Abl.…”
Section: Interaction With the Nuclear Envelope Protein Emerinmentioning
confidence: 99%